Homoeopathic Management of Bilateral Renal Calculi with Hydroureteronephrosis, Fatty Liver, And Adenomyosis in a Postmenopausal Woman: A Case Report (Homoeopathy for All, 2025)
Introduction: Renal calculi, hydroureteronephro sis, fatty liver, and adenomyosis are  common yet clinically challenging  conditions, particularly when occur ring concurrently in postmenopausal  women. Conventional treatment  often involves surgical or pharma cological interventions. This case  report highlights the role of indi vidualized homoeopathic manage ment in addressing this multisystem  presentation. Case Summary: A 50-year-old postmenopausal  woman with bilateral renal calculi,  hydroureteronephrosis, fatty liver,  and adenomyosis presented with  abdominal pain, pelvic heaviness,  flank pain, and vertigo. Based on her  totality of symptoms, Phosphorus was prescribed. Over two months,  she showed marked clinical and  radiological improvement. This  case highlights the potential of  individualized homoeopathic  treatment in managing complex  multisystem conditions.
Keywords: Conventional treatmen; improvement; multisystem conditions; physiological changes